Mobile Access to the Internet - Novikmec, J.; Dobos, L. (Radioengineering Society, 2002)
In this paper various aspects of mobile access to Internet are discussed. We mention general Internet protocols and mobile enhancements and also future models that will be used in near future.
Keywords: Mobile; IPv4; IPv6; Cellular IP; Mobile IPv6